Nystagmus during an acute Ménière's attack: from prodrome to recovery. (2nd January 2021) - Phillips, John S.; Newman, Jacob L.; Cox, Stephen J.; FitzGerald, John
Abstract: Objective: We are currently undertaking a clinical investigation to evaluate the diagnostic capability of a system for detecting periods of pathological dizziness. This article presents an analysis of the data captured during an acute attack of Ménière's disease. Design: The Continuous Ambulatory Vestibular Assessment (CAVA) device is worn by patients in the community, and continuously records eye and head movement data ( vestibular telemetry) . Study sample: A 53-year-old lady with a fifteen-year history of left-sided unilateral Ménière's disease. Results: The patient wore the device nearly continuously for thirty days. The data revealed a three-hour long attack of vertigo consisting of four separate phases of nystagmus. The duration, beat-direction and slow phase velocity of the nystagmus evolved through time. The first phase contained isolated nystagmus beats which preceded the patient's record of the vertigo attack onset but coincided with anticipation of an impending vertigo attack. Conclusions: CAVA provides a unique insight into the physiological parameters present during episodes of dizziness. Here, it has provided the first full example of an acute Ménière's attack, including a period of prodrome. These findings have implications for the prediction of vertigo attack onset, for the diagnosis of Ménière's disease and other diseases resulting in dizziness.